Fuzzy static fnite element analysis for functionally graded structures with semi-rigid connections - Pham, Hoang Anh (2020)
In this study, the fuzzy static behavior of functionally graded material (FGM) semi-rigid frame structures is freshly addressed. For the analysis purpose, a new FGM beam element with ﬂexible connections is established. Moreover, a computationally efcient procedure is developed to predict the fuzzy static structural behaviors. An FGM beam and an FGM planar frame involving fuzzy uncertainties in material properties, loads, and connection rigidities, are examined as numerical demonstrations. Fuzzy displacement responses are investigated. It is demonstrated that relatively accurate membership functions of the fuzzy displacements can be obtained by the proposed fuzzy procedure. The method proposed in this study is superior to the traditional vertex method and the global optimization approach in terms of computational efciency. Furthermore, it is revealing that the presence of uncertainties in connection rigidities can enlarge the fuzziness of the displacement outputs signifcantly.